British residents’ views about general practice care in France – a telephone survey - Pelletier-Fleury, Nathalie (BioMed Central, 2013)
BACKGROUND: Many studies have been published over the past decade on patients’ views about the provision of health care. Though there is a high level of migration within the European Union, there are no studies on migrants’ views about the provision of care in the country to which they moved. Given the wide spectrum of primary care in Europe, we hypothesised, without prejudging the outcome, that patients’ confidence in the system they left, used as a proxy of ‘the experience of care’, may influence their preferences regarding specific aspects of care in the host country. The objective of the study was to analyse British migrants’ views on general practice care in France. METHODS: A telephone survey was conducted with a random sample of the adult population of British people residing in France. Participants were 437 women and 423 men, aged 18 and over, who had consulted a general practitioner at least once during the past 12 months. The main outcome measures were the responses to the 23-item Europep questionnaire evaluating different aspects of general practice care, using a five-point answering scale with the extremes labelled as “poor” and “excellent”. RESULTS: Participants were generally satisfied with the GP care provided. The aspects that were rated the highest were related to the doctor-patient relationship which over 80% of the respondents judged as excellent or very good. Some aspects of the organisation of services received relatively negative evaluations. For instance, “waiting time in the waiting room” was evaluated as excellent or very good by only 40% of the respondents. Twenty seven percent of the respondents were not confident in the National Health Service (NHS) when they were still living in UK. After adjusting for age, sex and number of years of residence in France, the respondents who were not confident in the NHS provided a score of “excellent” significantly more frequently (on 11 out of the 23 aspects of care) than did the patients who were confident in the NHS. Most of these aspects concerned the doctor-patient relationship and information and support during the consultation. CONCLUSIONS: British migrants’ views on general practice care in France varied with the degree of confidence they had in the NHS. This finding is in line with the discussion on whether the ‘experience of care’ influences patient satisfaction. A better understanding of this phenomenon should provide valuable insights to make the services more responsive to the patients.